Le titre aborigène : émergence d’une figure nouvelle et durable du foncier autochtone ? - Otis, Ghislain (Les Cahiers de droit, 2005)
In the following paper, the author analyzes the central issues raised by the recognition of aboriginal title under State law. He offers answers to the many unresolved issues concerning the sources of aboriginal title, its conditions of existence and attributes. Concerning the sources of aboriginal title, the author highlights the Supreme Court’s stato-centric approach to the defnition of aboriginal rights and argues, in particular, that the doctrine of continuity of pre-colonial law has more of a metaphoric rather than operational meaning. As for the conditions of the title’s existence, the author concludes that they still remain sufficiently undetermined as to generate legal insecurity and allow judges to conduct, under the guise of an assessment of the historical record, contemporary socio-economic arbitrations between indigenous peoples and the non-indigenous majority. Finally, the analysis of the attributes of aboriginal title brings to light the uncertainty which persists with regard to several fundamental issues, such as, for example, the identity of the holder of title. This uncertainty of the law, as well as the failure of the Supreme Court of Canada to reconcile aboriginal title with modernity, cast doubt on the capacity of indigenous peoples to develop their lands according to their contemporary priorities.